Combating Narcotics Abuse by Children in Buleleng Regency - Dewa Gede Sudika Mangku; Ni Putu Rai Yuliartini (University of Udayana, 2021)
Drug abuse is a very worrying problem, especially for young people who will become the heirs and successors of the nation's struggle in the future. Narcotics abuse by children, especially in the Buleleng Regency area is high and is dominated by children aged 14-18 years who are still in school or still receiving education. The high number of narcotics abuse cases in Buleleng Regency at a young age has resulted in greater public concern due to its potentially damaging impact on all dimensions of life. The purpose of this study is to provide an effort to overcome narcotics abuse by children in Buleleng Regency. This research is an empirical legal research using a statutory approach. Based on the results of the study, it was found that the factors that influence narcotics abuse by children in Buleleng Regency are caused by internal and external factors and efforts to overcome them are carried out by penal efforts (legal channels) and non-penal efforts (non-legal channels.